Effect of malaria on cassava farmers' technical efficiency in Oyo state, Nigeria (2006)
The study analyses the effect of malaria on farmers' technical efficiency in Oyo State. A multistage simple random sampling technique was used to elicit information from 100 farmers. The Cobb-Douglas stochastic frontier production function was estimated for the farmers using the maximum likelihood method. The results revealed that an average farmer in the study area has malaria at least once a year and that treatment of malaria costs the farmer 21.39percent of his total income per incidence. Whereas land, labour and fertilizer were the major physical variables influencing the farmers technical efficiency, 'awareness of malaria, number of days of incapacitation due to malaria, use of preventive drugs were the other variables that affected the farmers' efficiency in the study area. Polio/ thrust of government should therefore be directed towards the provision of primary healthcare, sensitization on the prevention and treatment of malaria m order to improve the technical efficiency of the farmers in the study area